2006
DOI: 10.1901/jaba.2006.13-05
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Experimental Analysis of Academic Skills Deficits: Part Ii. Use of Brief Experimental Analysis to Evaluate Reading Fluency Treatments

Abstract: The technology of brief experimental analysis is just beginning to be used for identification of effective treatments for individual students who experience difficulty with oral reading fluency. In this study, the effect of a reading fluency treatment package was examined on easy and hard passages, and generalization was assessed on passages with high content overlap. The results suggest that the treatment package increased reading fluency for all 3 students. Effects were moderated by difficulty level for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Of the nine articles with cultural and/or language descriptors, 21 participants had a diagnosis of autism (63 %; e.g., Charlop-Christy et al 2002), whereas other articles reported those at risk for developmental delays (11 participants; 33 %; Pelaez et al 2011), individuals with referrals for reading problems (three participants; 9 %; Daly et al 2006), and an individual with Down syndrome (3 %; Emmick et al 2010). Of the 300 participants in the 103 studies that met inclusion criteria, the articles reported cultural background for 33 of those participants (11 %) and language background for three participants (1 %).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine articles with cultural and/or language descriptors, 21 participants had a diagnosis of autism (63 %; e.g., Charlop-Christy et al 2002), whereas other articles reported those at risk for developmental delays (11 participants; 33 %; Pelaez et al 2011), individuals with referrals for reading problems (three participants; 9 %; Daly et al 2006), and an individual with Down syndrome (3 %; Emmick et al 2010). Of the 300 participants in the 103 studies that met inclusion criteria, the articles reported cultural background for 33 of those participants (11 %) and language background for three participants (1 %).…”
Section: Resultsmentioning
confidence: 99%
“…Between the articles in JABA and TAVB with culture or language descriptors for participants, Caucasian (13 participants; 36 %; e.g., Emmick et al 2010) was the most commonly reported cultural background. Those from Hispanic descent (two participants; 5 %; e.g., Daly et al 2006) were the second most commonly reported cultural background. Two African-American participants were also represented (5 %; e.g., Ingvarsson and Hollobaugh 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BEA of oral reading fluency interventions has emerged as an empirically supported method for identifying effective oral reading fluency interventions for individual students (Daly, Bonfiglio, Mattson, Persampieri, & Foreman-Ya, 2006). A BEA of reading fluency interventions includes single intervention sessions for a variety of oral reading fluency interventions in an effort to identify an intervention strategy that is likely to be effective when implemented across numerous sessions (Daly, Martens, Hamler, Dool, & Eckert, 1999).…”
Section: Brief Experimental Analysismentioning
confidence: 99%
“…Brief experimental analysis (BEA) is an emerging technology that applies the principles and methods of experimental analysis and single‐case design to identify individualized interventions for students exhibiting deficits in academic behavior (Daly, Witt, Martens, & Dool, ). A growing body of research—mostly in reading—supports the use of BEA as a quick and reliable tool for differentiating academic interventions according to students’ individual needs (Daly, Bonfiglio, Mattson, Persampieri, & Foreman‐Yates, ; Daly, Martens, Hamler, Dool, & Eckert, ; Daly, Persampieri, McCurdy, & Gortmaker, ). To date, three general methods have been used to conduct BEAs with oral reading fluency deficits.…”
mentioning
confidence: 99%